Synchronous cancers of gallbladder carcinoma and combined hepatocellular cholangiocarcinoma: an unusual case and literature review - Zhang, Zhan-Guo (BMC Cancer, 2018)
BACKGROUND: Synchronous primary cancers in gallbladder and liver are rarely reported. Here we report an unusual case of synchronous cancers of gallbladder carcinoma and combined hepatocellular cholangiocarcinoma. CASE PRESENTATION: Several lesions in the gallbladder and in adjacent parenchyma of liver were discovered in a 65-years-old woman by imaging examination. Surgical resection was performed following a diagnosis of primary gallbladder carcinoma with local hepatic metastasis. Histological examination confirmed the diagnosis of primary gallbladder carcinoma, and the lesions in the liver consisted of hepatocellular carcinoma simultaneously with cholangiocarcinoma. Adjuvant chemoradiation therapy was not performed due to the patient’s refusal of the treatment. Unfortunately, the patient died of widespread metastasis 8 months after the operation. CONCLUSIONS: The disease needed to be differentially diagnosed from gallbladder carcinoma with hepatic metastasis. Aggressive surgical approach should be based on a balance between the risk of surgery (morbidity and mortality) and the outcome.